1999
DOI: 10.1002/hep.510290330
|View full text |Cite
|
Sign up to set email alerts
|

Ap53genetic polymorphism as a modulator of hepatocellular carcinoma risk in relation to chronic liver disease, familial tendency, and cigarette smoking in hepatitis B carriers

Abstract: This study evaluated whether the codon 72 p53 polymorphism was related to hepatocellular carcinoma (HCC). Genotypes of p53 were determined in 80 incident cases of HCC and 328 controls nested in a cohort study of 4,841 male chronic hepatitis B carriers. No overall increase in HCC risk with the Pro variant allele of the p53 polymorphism was apparent. However, there were synergistic effects on HCC development for the Pro allele with chronic liver disease and family history of HCC in first-degree relatives. Compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
83
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 33 publications
(71 reference statements)
7
83
0
2
Order By: Relevance
“…Among the more than 10 DNA sequence polymorphisms identified, the codon 72 polymorphism (Arg/Pro) has been explored in depth for a potential association with cancer. Although this polymorphism has been implied to be associated with certain cancer types (Yu et al, 1999;Fan et al, 2000;Shepherd et al, 2000), Sun et al (1999) reviewed 31 epidemiological case -control studies and suggested that codon 72 allelism did not have an impact on human cancer risk. The present study found that there was no significant difference in the frequency of codon 72 genotype between patients and referent controls (P ¼ 0.27).…”
Section: Discussionmentioning
confidence: 99%
“…Among the more than 10 DNA sequence polymorphisms identified, the codon 72 polymorphism (Arg/Pro) has been explored in depth for a potential association with cancer. Although this polymorphism has been implied to be associated with certain cancer types (Yu et al, 1999;Fan et al, 2000;Shepherd et al, 2000), Sun et al (1999) reviewed 31 epidemiological case -control studies and suggested that codon 72 allelism did not have an impact on human cancer risk. The present study found that there was no significant difference in the frequency of codon 72 genotype between patients and referent controls (P ¼ 0.27).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, familial clustering and early onset of HCCs in some populations suggest an inherited genetic predisposition to liver cancer [2]. Germline polymorphisms of several genes have been studied as potential risk factors for HCCs [3][4][5]. However, the pathogenesis of human HCC is a multistage process with the involvement of a series of genes, including oncogenes and tumor suppressor genes; germline polymorphisms of these genes may also determine individual susceptibility to HCC.…”
Section: Introductionmentioning
confidence: 99%
“…The P53 gene displays common polymorphisms in the general population, one of which, characterized by an Arg to Pro substitution at codon 72 in the transactivation domain of exon 4, has been investigated as risk modifier in several cancer models [17,18]. The variant Pro allele has been shown to be less efficient to suppress cell transformation and to induce apoptosis and to be less sensitive to degradation by viral oncogenic proteins [19].…”
Section: Viral Infections and Functional Inactivation Of P53 Codon 72mentioning
confidence: 99%
“…Intriguingly, Yu et al [17] found that P53 gene polymorphism involved in hepatocarcinogenesis may determine individual susceptibility to HCC. The P53 wild-type is polymorphic at residue 72 in exon 4, where a single-base change causes a substitution of Pro for Arg (CCC/CGC) in the transactivation domain [14].…”
Section: Viral Infections and Functional Inactivation Of P53 Codon 72mentioning
confidence: 99%